A Case Study: Strategies For Reducing Production Cycle Time - Tse, Ngu Ik (2009)
On the primary motivations for semiconductor cycle time improvement is to improve customer satisfaction. Few key success indicators are identified such as WIP level strategies, adata analysis, new loading strategies for low volume products, on hold management and management commitment to achieve shorter cycle time.